Profile of pediatric vasculitides – Prospective hospital-based data from eastern India - Arpan Saha; Sumantra Sarkar; Tanushree Mondal (Indian Journal of Rheumatology)
Background: The pediatric vasculitides are multisystem autoimmune disorders involving the blood vessels of varying sizes. Wide geographic and ethnic variations are noted in terms of incidence and clinical features. Materials and Methods: This prospective, observational study was carried out over a period of 4 years from 2015 February to 2019 February in a tertiary care referral hospital to delineate the epidemiological pattern, clinical features, and pathological characteristics of pediatric vasculitides. All consecutive patients with vasculitis defined by the American College of Rheumatology and Chappel Hill Consensus Criteria diagnostic criteria were included in the study. They underwent relevant investigations and were treated as per the standard guidelines. Results: Of the total 110 patients with different types of vasculitis, 90% (n = 99) had primary vasculitis and the rest had secondary (10%, n = 11). Immunoglobulin A vasculitis (Henoch–Schonlein Purpura) (HSP) (n = 53, 48.19%) and Kawasaki disease (KD) (n = 35, 31.82%) were the most frequent types of the vasculitis followed by Takayasu arteritis and polyarteritis nodosa. Secondary vasculitides included those associated with systemic lupus erythematosus, juvenile idiopathic arthritis, scrub typhus infection, and drug penicillamine. Various typical and atypical features along with a definite seasonal pattern of their prevalence had been documented. Conclusion: A profile of pediatric vasculitides with a specific trend in their prevalence and seasonal pattern has been documented. HSP and KD constitute the predominant types of pediatric vasculitides. KD, although diagnosed more often than previous, HSP still outnumbers KD in Eastern India.